Fundamental Approaches to Software Engineering 26th International Conference, FASE 2023, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2023, Paris, France, April 22-27, 2023, Proceedings - Lambers, Leen; Uchitel, Sebastián (Lecture Notes in Computer Science, 2023)
This open access book constitutes the proceedings of the 26th International Conference on Fundamental Approaches to Software Engineering, FASE 2023, which was held during April 22-27, 2023, in Paris, France, as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2023. The 12 regular papers presented in this volume were carefully reviewed and selected from 50 submissions. The proceedings also contain 2 tool papers, 2 NIER papers, and 2 competition papers from the Test-Comp Competition. The papers deal with the foundations on which software engineering is built, including topics like software engineering as an engineering discipline, requirements engineering, software architectures, software quality, model-driven development, software processes, software evolution, AI-based software engineering, and the specification, design, and implementation of particular classes of systems, such as (self-)adaptive, collaborative, AI, embedded, distributed, mobile, pervasive, cyber-physical, or service-oriented applications. .